Hubungan Literasi Digital dengan Berpikir Kritis Siswa dalam Pembelajaran PAI di SMKN 3 Payakumbuh - Rista Febrianti; Desti Sartini (Lembaga Yasin AlSys, 2026)
Digital literacy and critical thinking skills are essential competencies that students need to possess in addressing twenty-first-century learning. Although the relationship between these two competencies has been widely examined, research specifically analyzing the relationship between digital literacy and students’ critical thinking skills in Islamic Religious Education (PAI) learning at vocational high schools remains limited. This study aimed to analyze the relationship between digital literacy and students’ critical thinking skills in PAI learning at SMKN 3 Payakumbuh. The study employed a quantitative approach with a correlational survey design involving 57 respondents selected through simple random sampling. Data were collected using a digital literacy questionnaire and a critical thinking skills test that met the validity and reliability criteria. The data were analyzed using descriptive statistics, prerequisite tests, Pearson Product-Moment correlation, and the coefficient of determination with the assistance of IBM SPSS Statistics. The results showed a positive, very strong, and significant relationship between students’ digital literacy and critical thinking skills (r = 0.988; p < 0.05), with a coefficient of determination of 97.7%. These findings indicate that the higher students’ digital literacy, the higher their critical thinking skills in PAI learning. This study confirms that strengthening digital literacy is an important aspect of supporting the improvement of students’ critical thinking skills. Theoretically, these findings extend the literature on the relationship between digital literacy and critical thinking in the context of PAI learning, while practically, the results can serve as a basis for schools and PAI teachers to integrate digital literacy activities into technology-based learning processes.